HUBUNGAN SIKAP WANITA USIA SUBUR (WUS), DUKUNGAN SUAMI DAN PERAN PETUGAS DALAM PEMERIKSAAN IVA TEST - Nita Tri Putri; Maria Elfina (Maternal Child Health Care, 2022)
One of method to detect scervical cancer is by visual inspection of acetic acid with the community health center coverage of the Kolok in 2017, positive for 57 women of childbearing age and those who carried out visual inspection of acetic acid tests were two women (3.5%). this is evidence that there is still a lack of participation of women of childbearing age in early detection of cervical cancer because it is influenced by some factors including attitudes, husband's support and the role of health workers. Type of thus research is a cross-sectional descriptive analytic design with a sample of 74 women of childbearing age aged 15-49 years in the working area of the Kolok community health center with a probability sampling technique with proportional random sampling. This research was conducted on 9 to 25 January 2019. Data collection is carried out by observation and analysis with the chi-square test.The results of univariate analysis shows that 55.4% are positive, 63.5% husband's support, 59.5 % good health workers and 70.3% there is no visual inspection of acetic acid tests. The results of the bivariate analysis shows that there is a correlationship between husband support (p value 0.017 and OR 5.429) and the role of officers (p value 0.005 and OR 6.840) with a visual inspection of acetic acid tests. It can concluded that role of health workers has big influence toward examining inspection visual acetic acid test in the working area of community health centre KolokKeywords: husbands’ support, inpection visual acetic acid test, health workers’ role, attitude, women of childbearing age